Educating health professionals for cultural competence in emergency situations: A study protocol for a randomized controlled trial. (4th November 2019) - Slobodin, Ortal; Clempert, Neta; Kula, Yosef; Cohen, Odeya
Abstract: Aims: The current study is aimed at developing a culturally informed education program to increase cultural competence in emergencies among healthcare students and to examine its effectiveness using a randomized controlled trial. Design: This is a mixed‐methods study, which comprises two phases: (a) Development of educational intervention to increase cultural competence, based on a review of published scientific literature and primary data collection from qualitative semi‐structured interviews with key informants; (b) Implementation and assessment of the intervention effectiveness in increasing cultural competence in health students, using a randomized controlled trial. Methods: The qualitative phase will include semi‐structured interviews with 10 key informants. Data will be analysed using Interpretative Phenomenological Analysis. The assessment of intervention efficacy will be examined by a randomized controlled trial. This phase will include a total of 200 undergraduate health profession students who will be randomized (1:1 ratio) to intervention or non‐intervention group. Both study groups will complete pre‐ and postintervention questionnaires assessing three principles of cultural competence: attitudes, knowledge, and skills. The study is supported by 2‐year funding, beginning in September 2018. Discussion: Although the importance of culturally sensitive health services has long been recognized, there is a lack of cultural competence training in the medical education system, especially in the context of emergencies. Incorporating cultural competence education into the curricula offers an appealing strategy to enhance systematic understanding of cultural diversity at the early stages of professional training. Impact: The development of cultural competence training and curricula focusing on situations that may arise during emergencies may play a significant role in minimizing cultural dissonance, improve patient‐provider communication, and produce better clinical outcomes. Abstract : 目的: 此研究旨在开发一个文化教育项目, 以提高医疗卫生专业学生在医疗紧急情况下的文化能力, 并通过随机对照试验检验其有效性。 设计: 这是一项混合方法的研究, 研究包括两个阶段: (a)基于对已发表的科学文献的回顾和对关键信息提供者的定性半结构式访谈的原始数据收集, 发展教育干预以提高文化能力:(b)采用随机对照试验, 实施和评估干预措施在提高健康学生文化能力方面的有效性。 方法: 定性阶段将包括10名关键信息提供者的半结构式访谈。数据分析将使用解释性现象学分析。干预效果的评估将通过随机对照试验进行检验。这一阶段将包括200名卫生专业本科生, 他们将被随机(以1:1的比例)分为干预组和非干预组。两个研究小组将完成干预前和干预后的问卷调查, 该问卷调查用于评估文化能力的三个原则:态度、知识和技能。这项研究得到了从2018年9月开始为期两年的资金支持。 讨论: 虽然对文化敏感的卫生服务的重要性早已得到承认, 但在医学教育系统中缺乏文化能力培训, 特别是在紧急情况下。在专业培训的早期阶段, 将文化能力教育纳入课程也是一种有吸引力的策略, 以增强职业训练早期学生对文化多样性的系统理解。 影响: 发展文化能力培训和课程并重点关注紧急情况下可能出现的情况, 可在最大程度地减少文化不和谐、改善患者‐提供者沟通、产生更好的临床结果方面发挥重大作用。